Formation of social communication skills among students of the Faculty of Medicine in the system of professional education. Experience of the Republic of Kazakhstan - K. Kidirbayeva; Sh Satiyeva; Zh Kuanyshbayeva; A. Iskakova; G. I. Assanova; G. Роvalyashko; Zh. Duisenbekova (Кардиоваскулярная терапия и профилактика, 2023)
The article describes the formation of social communication (SC) skills among healthcare professionals in order to determine its place in professional activities.A theoretical analysis of the philosophical, pedagogical, psychological and scientific-methodical literature related to the problem under study was carried out. The national pedagogical experience in SC development was analyzed through the prism of cultural and moral patterns embedded in the national literature. The following methods were used: conversations with students, medical workers, discussion, survey.According to the authors, the low interest in national literature and culture is a significant reason for the low level of SC skills among workers in the social and medical service and in professional group communication. A survey among students showed a low interest in the national cultural samples, including those expressed in national literature.According to the authors, in the development of SC skills in future healthcare professionals, the experience of domestic pedagogy is of great importance, aimed at improving the moral education necessary for adequate behavior and communication, not only in the context of local and national realities, but also including respect for other cultures.